ANALISIS KUALITAS WEBSITE PUSAT KARIR ITN MALANG DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - Deddy Rudhistiar; Reiny Myrtanti; Ida Bagus Suardika (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
A websites in the development of information technology makes it easier to find information effectively and efficiently. Until now the website is also used within the scope of a university or institution. An institution can use a website as a means of information and communication that can be accessed by everyone. Career Center National Institute of Technology Malang, is one of the institutions in charge of serving alumni and tracer study. This institution implements a website as a medium for disseminating information about alumni, tracer study and job fairs, as well as job vacancies in accordance with the Study Program at National Institute of Technology Malang. The purpose of this study is to determine the quality of the Career Center National Institute of Technology Malang website, by analyzing and measuring the quality value of the Career Center website. The method used in this study is the WebQual 4.0 method with the object being studied is the Career Center website. The number of respondents is 147 people who come from students, alumni, lecturers and employees as well as the general public with data collection techniques using questionnaires. The variables used in this research are usage, information service quality, website design, and interaction service quality, as well as user satisfaction. Based on the questionnaire analysis using the WebQual 4.0 Method and Importance Performance Analysis with 5 variables used, the mapping results into 4 (four) quadrants, namely quadrants I, II, III, and IV. According to user perception, it is expected that the institution will prioritize the most influential quadrant I to make improvements/additions/changes to the Information Dimension, in providing accurate, timely, and relevant information.